Antiangiogenesis for Advanced Non-Small-Cell Lung Cancer in the Era of Immunotherapy and Personalized Medicine - Tabchi, Samer; Blais, Normand (Frontiers in Oncology, 2017)
Over the past decade, patients with advanced non-small-cell lung cancer (NSCLC) have witnessed substantial advances in regards to therapeutic alternatives. Amongst newly developed agents, angiogenesis inhibitors were extensively tested in different settings and have produced mostly favorable outcomes despite some shortcomings. Bevacizumab is the most examined agent in this context and has demonstrated significant survival benefits when combined with standard chemotherapy in eligible patients. Preliminary results on the addition of bevacizumab to erlotinib in patients with EGFR-mutated NSCLC seem promising. Other anti-angiogenic agents were also tested but ramucirumab and nintedanib are the only agents with a positive impact on survival. More recently, immune-checkpoint inhibitors have had considerable success due to their prolonged durations of response, yet response rates are still deemed suboptimal and various combination therapies are being tested in an effort to improve efficacy. Preclinical evidence suggests an immunosuppresive effect of pro-angiogenic factors which sets up a plausible rationale for combining immune checkpoint inhibitors and anti-angiogenic agents. Herein, we review the landmark data supporting the success of angiogenesis inhibitors and we discuss the potential for combination with immunotherapy and targeted agents.